Egalitarian Communication in the Leadership of Muhammad SAW: A Transformative Model for a Multicultural Society of the 21st Century - Zaman, Toyiz (Jurnal Indonesia Sosial Sains, 2025)
Contemporary leadership faces unprecedented challenges in managing increasingly diverse and interconnected global societies, particularly in addressing communication barriers across cultural, religious, and ethnic divides. The rise of social polarization, intercultural conflicts, and the failure of traditional hierarchical leadership models necessitate the exploration of alternative approaches that can effectively bridge differences while promoting inclusive participation. This research examines the egalitarian communication model in the leadership of Prophet Muhammad (PBUH) and its relevance as a transformative model for a multicultural society in the 21st century. Using qualitative methodology with a historical-philosophical approach through literature study, this research analyzes the communication principles practiced by Prophet Muhammad in building an inclusive and egalitarian society. The findings reveal that Prophet Muhammad's communication model is characterized by equality, inclusivity, active listening, empathetic dialogue, and respect for diversity. These principles remain highly relevant as a foundation for effective communication in today’s multicultural society. This research contributes to Islamic communication studies and offers practical solutions for leadership challenges in the contemporary era.